Intra- and Intergenerational Aspects of Serious Domestic Violence and Alcohol and Drug Abuse in Buffalo, 1987 - Blane, Howard T. ([Verlag nicht ermittelbar], 1993)
These data examine the interrelationships among alcohol use, drug use, criminal violence, and domestic violence in a parolee population. More specifically, the data explore the contributions of parental substance abuse and domestic violence in prediction of parolee violence. The study also investigates the effects of drug and alcohol use on domestic violence for the parolee, the spouse, and the parents. The data were drawn from individual interviews conducted with parolees from the Buffalo, New York, area, half of whom were convicted of violent crimes and half of whom were convicted of nonviolent crimes. Interviews were also conducted with the spouses and partners of the parolees. In addition, data concerning the parolees' criminal histories were abstracted from arrest and parole records. Part 1, Demographic File 1, provides information on the demographic characteristics of offenders, arrests, convictions, and sentencing, institutional transfers, disciplinary reports, indications of psychiatric diagnosis or psychological disturbances, alcohol and drug use, criminal activity, and substance abuse while incarcerated. Part 2, Demographic File 2, includes the same variables as Part 1 (with the exception of information about psychiatric diagnoses, psychological disturbances, and disciplinary reports) for those individuals who declined to be interviewed and a random sample of those who could not be contacted. Part 3, the Interview File, contains information about childhood social histories (including sociodemographics, experience of family violence as a victim and as a witness, and parental drug and alcohol use), self-reported criminal histories, adult social histories (including data concerning violence in current relationships, and drug and alcohol use history), and information about the parolees' and spouses' discipline styles. The researchers discarded data on female parolees for the purposes of their analysis.